Transport of soluble surfactant on and within a foam film in the context of a foam fractionation process. (16th January 2023) - Rajabi, Hamed; Grassia, Paul
Graphical abstract: Highlights: Foam fractionation with reflux is modelled for a soluble surfactant. Reflux induces Marangoni-driven surfactant transfer from Plateau border to film. Two isotherms (global and local Henry) relate surfactant on and within foam film. Surfactant transfer slowed by solubility and by local Henry isotherm. Film drainage reduces surfactant recovery but improves enrichment. Abstract: This study models soluble surfactant transport on and within a foam film during a foam fractionation process. Marangoni flow drives surfactant onto the film, and also surfactant concentration is assumed to be uniform across the thin foam film. Adsorption isotherms are used to couple mass transfer equations, so as to determine the evolution of the total amount of surfactant (surface plus bulk) at any film location. Surfactant transport is considered both in the absence and presence of film drainage. It is observed that having soluble surfactant slows down evolution of Marangoni-driven flow compared to cases assuming insoluble surfactant. This is because in soluble surfactant cases, surfactants diffuse to the bulk even whilst being transferred by Marangoni flow onto the film surface. Furthermore, it is observed that a quasisteady state typically occurs after a long time, such that Marangoni flow and film drainage flow become comparable.